Effect of mindfulness meditation on depression during pregnancy: A meta-analysis - Li, Yuchao; Chen, Jinghui; Chen, Baoxia; Wang, Tingting; Wu, Zhusheng; Huang, Xia; Li, Shanshan (Frontiers in Psychology, 2022)
Purpose: This study systematically evaluates the effect of mindfulness meditation on depression during pregnancy. We provide evidence-based suggestions for preventing and reducing depression during pregnancy by exploring the most effective intervention mode, cycle, and frequency of mindfulness meditation. Methods: Records were retrieved from PubMed, Web of Science, EBSCO, and Science Direct. A total of 1612 randomised controlled trial studies on the effect of mindfulness meditation on pregnancy depression were collected. 10 studies with 658 subjects meeting the inclusion criteria were extracted and analysed by Revman 5.3 to evaluate study qualities. Stata 12.0 was used for the meta-analysis. Results: Mindfulness meditation had a positive effect on depression during pregnancy (standardised difference of the mean [SMD] = -0.786, 95% confidence interval [- 1.289, - 0.283], P < 0.001). Subgroup analysis showed that mindfulness-based cognitive therapy (MBCT) had the best intervention effect on depression during pregnancy (SMD = 2.795), the best intervention duration was below 4 weeks (SMD = 1.756), applied from the first to the third stage of pregnancy (SMD = 1.024), the frequency guided by experts was less than six times a week (SMD = 2.055) of less than 60 min each time (SMD = 1.068), and completing homework by themselves every day for 30 minutes (SMD = 1.822) was most significant for the improvement of depression during pregnancy. We found high heterogeneity across studies [q = 97.003, DF = 10, I2 = 88.0% (P < 0.001), I2 > 75%]. This may be caused by variance in measurement tools, among which Beck Depression Inventory--II was a significant source of heterogeneity. Conclusion: Mindfulness meditation can improve the prevention, remission, and reduction of depression during pregnancy and can be used as an auxiliary measure for the clinical treatment of pregnancy depression.